Double acute appendicitis: cecal and epiploic; literature review of a case report - Pinzon, Camilo Levi Acuna; Chavaria Chavira, Jose Luis; Nieves Condoy, Jefferson Fabian; Ledesma, Claudia Ortiz (International Journal of Research in Medical Sciences, 2020)
Acute cecal appendicitis and appendagitis are two entities due to the inflammation of the cecal and epiploic appendix respectively. A case of a 34-year-old woman is presented, who is admitted for abdominal pain. Initial blood test and ultrasonography were not conclusive, subsequently with clinical deterioration, surgical intervention was required which noted acute appendicitis and appendicitis that were removed. This is an extremely unusual case, since the simultaneous presentation of these two entities has not been widely described and demonstrates the importance of exploring the abdominal and pelvic cavity in patients with suspected diagnosis of acute appendicitis.